2002
DOI: 10.1177/014616702236873
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Judgments of Fairness in a Real-World Political Context: A Test of the Value Protection Model of Justice Reasoning

Abstract: Current theories of justice emphasize social identity reasons for why people care about justice to the relative neglect of personal identity concerns, that is, people's need to express, defend, and live up to personal moral standards. The authors present a value protection model that predicts that self-expressive moral positions or stands ("moral mandates") are important determinants of how people reason about fairness. Hypotheses were tested and supported in the context of a natural experiment: reactions of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
227
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(241 citation statements)
references
References 18 publications
10
227
4
Order By: Relevance
“…Skitka and Mullen argue that moral positions or stands (moral mandates) are important determinants of how people think about fairness. Both in a real life case (Elian Gonzalez case, Skitka and Mullen 2002) and with regards to a number of political issues (Skitka 2002), the model was supported. Skitka found that having a moral mandate on abortion, civil rights or immigration was not linked to procedural justice judgments of the political institutions concerned with these topics, as long as those institutions posed no concrete moral value threat to these concerns.…”
Section: Individual Morality and Its Relationship With Just Actions Amentioning
confidence: 79%
See 1 more Smart Citation
“…Skitka and Mullen argue that moral positions or stands (moral mandates) are important determinants of how people think about fairness. Both in a real life case (Elian Gonzalez case, Skitka and Mullen 2002) and with regards to a number of political issues (Skitka 2002), the model was supported. Skitka found that having a moral mandate on abortion, civil rights or immigration was not linked to procedural justice judgments of the political institutions concerned with these topics, as long as those institutions posed no concrete moral value threat to these concerns.…”
Section: Individual Morality and Its Relationship With Just Actions Amentioning
confidence: 79%
“…In the value protection of justice model (Skitka and Mullen 2002), personal identity concerns are an important antecedent to justice motives and judgments (while most at the literature looks at social identity reasons). Skitka and Mullen argue that moral positions or stands (moral mandates) are important determinants of how people think about fairness.…”
Section: Individual Morality and Its Relationship With Just Actions Amentioning
confidence: 99%
“…Only recently has this research started to identify (self-related) boundary conditions to the effects of procedural fairness. This empirical wave indicates that the impact of procedural fairness is reduced when decision outcomes violate central aspect of one's identity or strong moral convictions (Mayer et al, 2009;Skitka & Mullen, 2002). Yet, other work suggests that procedural fairness matters even when decision outcomes go against strongly held convictions (Napier & Tyler, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Research on moral mandates may corroborate this assumption showing that personal moral values have a high action potential (SKITKA, 2002;SKITKA;HOUSTON, 2001;SKITKA;MULLEN, 2002). Skitka and colleagues showed that the value-behaviour link is especially strong for individuals with moral mandates which are selective expressions of values and central to people's sense of personal identity.…”
Section: Personally Desired Versus Personally Desirablementioning
confidence: 94%
“…People who develop moral mandates are highly motivated to express and protect them. Skitka and Mullen's (2002) examined reactions of US-American adults to the Elian Gonzales case who became the centre of a heated public controversy and custody battle between his father in Cuba and his extended family in the USA. People in both the USA and Cuba engaged in demonstrations to defend their divergent position and values on the same issue.…”
Section: Personally Desired Versus Personally Desirablementioning
confidence: 99%